A Taxonomic Analysis of the Structure of Prime Costs in Polish Clinical Hospitals - Sikora-Alicka Joanna (Sciendo, 2021)
Research background: The analysis of the genesis and the way of defining clinical hospitals allows us to conclude that the evaluation of their activities should consider many criteria, not only the treatment process in itself. Activities characteristic for a clinical hospital include, apart from the medical, also prophylaxis and preventative measures, preceded by the identification of health risks, soliciting research and creating new directions of medical research, as well as implementing new medical technologies and treatment methods (Article 3, paragraph 2, points 1–2, Journal of Laws of 2020, items 295, 567, 1493, 2112, i.e.) combined with the training of medical personnel. Which all makes those units unique among hospitals.